2018
DOI: 10.1002/mabi.201800167
|View full text |Cite
|
Sign up to set email alerts
|

Composite Biomaterials as Long‐Lasting Scaffolds for 3D Bioprinting of Highly Aligned Muscle Tissue

Abstract: New biocompatible materials have enabled the direct 3D printing of complex functional living tissues, such as skeletal and cardiac muscle. Gelatinmethacryloyl (GelMA) is a photopolymerizable hydrogel composed of natural gelatin functionalized with methacrylic anhydride. However, it is difficult to obtain a single hydrogel that meets all the desirable properties for tissue engineering. In particular, GelMA hydrogels lack versatility in their mechanical properties and lasting 3D structures. In this work, a libra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
139
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 117 publications
(141 citation statements)
references
References 66 publications
2
139
0
Order By: Relevance
“…Poly(vinyl alcohol)(PVA)‐alginate has also been used to bioprint constructs with micropores showing controlled release of proteins . In another study, Ramon‐Azcon and colleagues developed a library of composite biomaterials used as bioinks and showed that GelMA‐carboxymethyl cellulose methacrylate (CMCMA) allowed the growth and differentiation of encapsulated C2C12, while presenting high resistance to degradation . Moreover, microfluidic print heads have also been used to deposit multiple materials into microfibers or droplets.…”
Section: Skeletal Muscle Tissue Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…Poly(vinyl alcohol)(PVA)‐alginate has also been used to bioprint constructs with micropores showing controlled release of proteins . In another study, Ramon‐Azcon and colleagues developed a library of composite biomaterials used as bioinks and showed that GelMA‐carboxymethyl cellulose methacrylate (CMCMA) allowed the growth and differentiation of encapsulated C2C12, while presenting high resistance to degradation . Moreover, microfluidic print heads have also been used to deposit multiple materials into microfibers or droplets.…”
Section: Skeletal Muscle Tissue Engineeringmentioning
confidence: 99%
“…[90] In another study, Ramon-Azcon and colleagues developed a library of composite biomaterials used as bioinks and showed that GelMA-carboxymethyl cellulose methacrylate (CMCMA) allowed the growth and differentiation of encapsulated C2C12, while presenting high resistance to degradation. [91] Moreover, microfluidic print heads have also been used to deposit multiple materials into microfibers or droplets. This technique allows fast switching between different bioinks as well as the formation of fibers with different coded bioink segments or heterogeneous fibers with two or more parallel bioinks in the fiber.…”
Section: • Prepatterning Of Acetylcholine Receptorsmentioning
confidence: 99%
“…Methacrylated gelatin (GelMA), a photocrosslinkable hydrogel derived from natural gelatin, emulates the ECM for various cells types in combination with non-biodegradable materials such as alginate. We used the synthesis process as previously described 43 . Briefly, Gelatin (Sigma-Aldrich, USA) was modified to a 40% degree of methacrylation.…”
Section: Synthesis Of Hydrogelsmentioning
confidence: 99%
“…The alginate/nano-cellulose bioink system, including variations such as sodium alginate [268], alginate sulphate [267], and the various phases of nano-cellulose, have been reported to have better performance than, for example, hyaluronic acid/nano-cellulose [266]. Gelatin/nano-cellulose based bioinks combined with oxidation also have no cytotoxicity, a pore size of~600 µm, good cell viability, improved mechanical properties (compressive modulus from 0.5 to 8.5 kPa with the addition of 2% w/v nano-cellulose), and improved print properties [284][285][286]. PEGDA/nano-cellulose structures fabricated by SLA showed high NIH 3T3 cell viability [274].…”
Section: Biocompatibility Biodegradability and Bioactivitymentioning
confidence: 99%